Paradoxes of segregation : housing systems, welfare regimes and ethnic residential change in Southern European cities - Arbaci, Sonia (Studies in Urban and Social Change, 2019)
Through an international comparative research, this unique book examines ethnic residential segregation patterns in relation to the wider society and mechanisms of social division of space in Western European regions. * Focuses on eight Southern European cities, develops new metaphors and furthers the theorisation/conceptualisation of segregation in Europe * Re-centres the segregation debate on the causes of marginalisation and inequality, and the role of the state in these processes * A pioneering analysis of which and how systemic mechanisms, contextual conditions, processes and changes drive patterns of ethnic segregation and forms of socio-ethnic differentiation * Develops an innovative inter-disciplinary approach which explores ethnic patterns in relation to European welfare regimes, housing systems, immigration waves, and labour systems